Aspects of the emergence ecology of the regionally endangered Coenagrion mercuriale (Odonata: Coenagrionidae) in Northeast Algeria. Issue 3 (3rd July 2018) - Mellal, Mohammed Khalil; Zebsa, Rabah; Bensouilah, Mourad; Houhamdi, Moussa; Khelifa, Rassim
ABSTRACT: Emergence is a critical phase in the life cycle of odonates because then they are highly susceptible to predation and damage. Thus the ecological understanding of this phenomenon is crucial, particularly for the conservation and management of threatened species. We studied the emergence ecology of the regionally endangered damselfly ( Coenagrion mercuriale ) in Northeast Algeria where the species produces two generations per year (spring and autumnal), focusing on the temporal emergence pattern, body size and vertical stratification of exuviae of the autumnal population. Emergence was synchronous with 50% of the population emerging within eight days. Sex ratio at emergence was slightly female biased. A seasonal decline was observed in the body size of the autumnal population like in that of the spring population. Vertical stratification of exuviae at ecdysis depended on the height of the support and vegetation density. These data are expected to be important for the management and conservation of this threatened species in Northeast Algeria and elsewhere within the distribution range.